An Analysis of the Orange Technology Approach in Short Video-Based Digital Marketing Strategies - Untung Rahardja; Galih Putra Cesna; Rani Nuraeni; Michael Surya Gunawan; Jonathan Parker (ADI Publisher, 2026)
Short video platforms such as TikTok, Instagram Reels, and YouTube Shorts have become strategic media in digital marketing, particularly for skincare products that are highly popular among millennials. This trend highlights that marketing is no longer limited to information delivery but also involves building emotional connections, consumer trust, and digital literacy. This study aims to analyze the influence of short video marketing on skincare purchase decisions using the Orange Technology approach, which emphasizes empathy, transparency, and consumer well-being. The method employed is a descriptive qualitative approach through literature review and thematic analysis to examine the roles of visual, narrative, and interactivity elements within short video content. The findings indicate that short video marketing is effective in enhancing brand awareness, reinforcing product recall, and fostering emotional and social engagement with consumers. However, risks such as misinformation, visual manipulation, and low digital literacy require the implementation of ethical principles and consumer education. In conclusion, when designed ethically, empathetically, and transparently, short video marketing is not merely a promotional tool but also a practical application of Orange Technology that supports innovation, humanistic values, and consumer well-being. Therefore, this strategy contributes both to strengthening purchase decisions and maintaining consumer trust.